Social spending as a development tool: Evidence from developing countries - Deepti Ahuja; Deepak Pandit (European Journal of Government and Economics (EJGE), 2022)
In this paper, we aim to study the interrelationship between social spending, economic growth, and income inequality in developing countries from the year 1990 to 2013. We observed that all the categories of social spending produced a significant reduction in income inequality. Further, the impact of health and education spending on economic growth is significant, and that of social protection is insignificant. This indicates that both health and education spending can break the trade-off between equity and efficiency, that is, it can lead to both growth and progressive distributional change. However, given the importance of social welfare measures in reducing income inequality, developing countries need to focus on active social spending like labor market reforms that can increase gross domestic product growth rate and simultaneously reduce income inequality.
Keywords: C33; D30; H51; H52; O40; 330; social spending; income inequality; GDP growth; simultaneous equation model; Asia-Pacific countries